Enhancing the performance of a PtPd/HY catalyst for HDPE/VGO hydrocracking through zeolite desilication - Vela, Francisco J. (2022)
The valorization of post-consumer waste plastic in a refinery is an attractive initiative to avoid environmental problems caused by the poor plastic waste management. The modification of a bifunctional PtPd/HY catalyst through desilication (using NaOH) of the ultrastable HY zeolite has been carried out to upgrade waste plastic (high-density polyethylene (HDPE)) dissolved in a secondary refinery stream (vacuum gas oil (VGO)) through hydrocracking. Three different catalysts have been studied: the parent (Cat-A), undergoing a desilication cycle (Cat-B), and subjected to two cycles of desilication (Cat-C). The characterization techniques employed have been: N2 adsorption–desorption, TEM, ICP-AES, tert-butylamine-TPD, pyridine FTIR, WDXRF, XRD and TPO. The hydrocracking tests have been carried out in a semi-batch reactor at: 440 °C; 80 bar; catalyst to feed ratio, 0.1 gcat (gfeed)–1; HDPE to feed ratio, 0.2 gHDPE (gfeed)–1; and reaction time, 2 h. The products have been fractioned according to their boiling point range in: gas, naphtha, light cycle oil, heavy cycle oil and coke. The composition of each fraction has been determined in terms of concentration of paraffins, olefins, naphthenes and (mono-, di- and poly-) aromatics. The results show that alkaline treated catalysts enhance the fuel production, with high HDPE and HCO conversions. The Cat-C (the one submitted to two desilication cycles) has displayed the greatest performance, reducing by half the gas yield and increasing the naphtha yield by 51 wt% respect to those obtained with the parent catalyst (Cat-A). Moreover, it has decreased the coke deposition and the coke formed has been less developed.